LOS CONTORNOS MELÓDICOS COMO SEÑALIZADORES DE LA FUERZA ILOCUTIVA DEL DISCURSO DEL PROFESOR DE L2 - Fonseca Mora, María Carmen (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract L2 teachers often have difficulties in communicating successfully in the target language with students who have poor transitional competence. However, in a former study, Fonseca and Cuenca (2000) observed that it was possible for a native English teacher to communicate with seven-yearold beginners whose mother tongue was Spanish by using a type of simplified code created to help the hearer to learn and understand language. One of the features identified in that code was the use of exaggerated melodic contours to show the teacher’s illocutionary intention. The main purpose of this paper is to present the results of the analysis of the speech melodies used by twenty native and non-native teachers teaching English as a foreign language in Spain. This research is based on findings in first language acquisition papers that argue that those melodic contours, identified in child-directed speech, are used intuitively by parents to guide their babies’ musical beginnings (Papousek, 1996), but also as a speciesspecific learning guide to language (Snow, 1972; Stern at al., 1982; Papousek, 1994; Feu and Piñero, 1996). The conclusions of this study imply that the prototypical contour variations found in the data are based on shared knowledge between teachers and students.